2010
DOI: 10.1371/journal.pmed.1000287
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Biological and Behavioural Impact of an Adolescent Sexual Health Intervention in Tanzania: Follow-up Survey of the Community-Based MEMA kwa Vijana Trial

Abstract: David Ross and colleagues conduct a follow-up survey of the community-based MEMA kwa Vijana (“Good things for young people”) trial in rural Tanzania to assess the long-term behavioral and biological impact of an adolescent sexual health intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 26 publications
7
128
0
Order By: Relevance
“…In comparison to less comprehensive programmes, CSE has been shown to contribute more adequately to gains in young peoples' sexual health (Fine and McClelland 2006;Haberland and Rogow 2015;kirby 2008;McCave 2007;Trenholm et al 2007;Underhill, Montgomery, and Operario 2007). However, evidence of the (long-term) effects of CSE on young people's protective behaviours and certainly on biomarkers, such as the prevalence of STIs/HIV and teenage pregnancies, is at most only moderately strong, often even weak (Doyle et al 2010;kirby 2007;kohler, Manhart, and lafferty 2008;UNFPA 2010;Yankah and Aggleton 2008). Reasons brought forward to explain these modest results are related to limitations in the content, implementation and delivery of educational programmes, to disabling environments and the complex cultural embeddedness of sexual behaviours, as well as to methodological problems in the studies conducted (kippax 2003;Michielsen et al 2010;Vanwesenbeeck 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to less comprehensive programmes, CSE has been shown to contribute more adequately to gains in young peoples' sexual health (Fine and McClelland 2006;Haberland and Rogow 2015;kirby 2008;McCave 2007;Trenholm et al 2007;Underhill, Montgomery, and Operario 2007). However, evidence of the (long-term) effects of CSE on young people's protective behaviours and certainly on biomarkers, such as the prevalence of STIs/HIV and teenage pregnancies, is at most only moderately strong, often even weak (Doyle et al 2010;kirby 2007;kohler, Manhart, and lafferty 2008;UNFPA 2010;Yankah and Aggleton 2008). Reasons brought forward to explain these modest results are related to limitations in the content, implementation and delivery of educational programmes, to disabling environments and the complex cultural embeddedness of sexual behaviours, as well as to methodological problems in the studies conducted (kippax 2003;Michielsen et al 2010;Vanwesenbeeck 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, data on effects of lessons regarding SRH given in school on outcomes later in life are very inconclusive, and much of this research has been conducted specifically in response to the HIV epidemic in sub-Saharan Africa (e.g. Doyle et al 2010).…”
Section: Interactions Between Sexual and Reproductive Health And Educmentioning
confidence: 99%
“…We identified 11 interventions in schools that had been published in 2005-2008 and met our criteria for inclusion (A, B, E-M) [11,13,[17][18][19][20][21][22][23][24][25]. Of these 11, five were in South Africa, three in Kenya, and there was one intervention each in United Republic of Tanzania, Uganda, and Zimbabwe.…”
Section: Interventions In Schoolsmentioning
confidence: 99%
“…None of the studies attempted to explore the relationship or relative contribution of different aspects of health facility improvements versus community activity, on uptake of health services. The scale of the interventions included in this review varied widely, with the smallest providing services in 10 communities [11], and the largest including a network of 146 health facilities [33]. There were two studies of type 1c and five studies of type 2c, but no interventions of types 1a, 1b, 2a, or 2b were identified.…”
Section: Interventions In Health Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation